Practice implications and recommendations for managing codeine misuse and dependence - Bergin Michael; Norman Ian; Foley Michelle; Harris Richard; Rapca Anna; Rich Eileen; Hout Marie-Claire Van (Acta Pharmaceutica)
Codeine, a weak opiate, requires increased pharmacovigilance relating to availability, heterogeneous nature of misuse, dependence and associated harm. A scoping review of literature on codeine was conducted using Arksey & O’Malley’s framework (1). Databases searched included PubMed, EBSCO Host, Science Direct, EMBASE, PsycINFO, Cochrane library and Medline from 1994 to 2014. Follow-up search strategies involved hand searching and searching of pharmaceutical, health, medical and drug related websites. Initial zscreening identified 3,105 articles with 475 meeting the inclusion criteria. Eight broad categories organised the literature, data charting and qualitative synthesis. This paper presents implications for practice and makes recommendations to address these issues. Themes identified relate to raising public and practitioner awareness, risk management, dispensing practices and monitoring and surveillance of codeine. Evidence to inform law enforcement, drug surveillance, public health initiatives, harm reduction approaches, pharmacy, clinical and treatment practices is warranted.